LEXICAL COHESIVE DEVICES IN NEWS STORY TEXTS OF THE DAILY ANALISA - Finky Sahputra Sinaga; Amrin Saragih; Juli Rachmadani Hasibuan (LINGUISTICA, 2019)
This study dealt with lexical cohesive devices in News Story Text of Daily Analisa. It employed descriptive qualitative research method. The news story textsis analyzed using cohesive devices theory by Michael Halliday and Ruqaiya Hasan. This study was aimed to analyze: (1) The kinds of Lexical Cohesive Devices which are used in News story texts of the Daily Analisa (2) How Lexical Cohesive devices used in News story text of The Daily Analisa. The result shows that not all lexical cohesive devices types are used in news story text. The findings are only has three types of the cohesive devices in the text. Based on the analysis, the lexical cohesive devices ties in the text construct the unity as well as the context in the text. in the other words, the lexical cohesive devices makes the text function in which it is embedded. It can be said that the lexical cohesive devices create the coherence of the textKeywords: coherence,context, daily Analisa, discourse analysis,lexical cohesive devices, news story texts